Intimate partner violence against adolescent girls and young women and its association with miscarriages, stillbirths and induced abortions in sub-Saharan Africa: Evidence from demographic and health surveys - Bright Opoku Ahinkorah (SSM: Population Health, 2021)
Intimate partner violence has been associated with numerous consequences for women, including pregnancy termination. This study aimed to examine the association between intimate partner violence and pregnancy termination among adolescent girls and young women in 25 sub-Saharan African countries. Data for this study was obtained from the demographic and health surveys of 25 countries in sub-Saharan Africa, published between 2010 and 2019. A total of 60,563 adolescent girls and young women were included in this study. Binary logistic regression models were used in analyzing the data and the results were presented as crude odds ratios (CORs) and adjusted odds ratios (AORs) at 95% confidence interval (CI). The prevalence of intimate partner violence and pregnancy termination among adolescent girls and young women in the 25 countries in sub-Saharan Africa were 19% and 10.1% respectively. In all these countries, the odds of pregnancy termination was higher among adolescent girls and young women who had ever experienced intimate partner violence, compared to those who had never experienced intimate partner violence [COR = 1.60, 95% CI = 1.51–1.71], and this persisted after controlling for confounders [AOR = 1.58, 95% CI = 1.48–1.68]. However, across countries, intimate partner violence had significant association with pregnancy termination among adolescent girls and young women in Angola, Chad, Congo DR and Gabon (Central Africa); Benin, Burkina Faso, Cote D'lvoire, Gambia and Mali (West Africa); Comoros, Rwanda and Uganda (East Africa); and Malawi and Zambia (Southern Africa). The findings imply that reducing pregnancy termination among adolescent girls and young women in sub-Saharan Africa depends on the elimination of intimate partner violence. Thus, policies and programmes aimed at reducing pregnancy termination among adolescent girls and young women in sub-Saharan Africa, should pay particular attention to those who have history of intimate partner violence.